Molecular Characterization and Pathogenicity of Colletotrichum on Banana Fruits: Wound Effects on Virulence and Cross-Infection - Maysa C. Santos; Luis O. Viteri; Sabrina H. Araujo; Dalmarcia C. Mourão; Marcos P. Câmara; Ana G. Amaral; Eugênio E. Oliveira; Gil Rodrigues dos Santos (Microbiology Research)
For this article, we evaluated whether wounds would affect the pathogenicity and virulence of Colletotrichum sp. isolates on Musa spp. banana cultivars. We further assessed the potential of cross-colonization with other fruit species and investigated the molecular and phylogenetic characterization of the most virulent isolates. Firstly, we collected dwarf bananas showing anthracnose symptoms from commercial markets in the city of Gurupi, Tocantins State, Brazil, and isolated Colletotrichum sp. under controlled conditions prior to identification. The virulence was assessed on wounded and unwounded banana fruits, identifying the most virulent isolate by exposure tests on fruits of the “prata”, “maçã”, “marmelo”, and “terra” banana cultivars. We also subjected specimens of mango (Mangifera indica), papaya (Carica papaya), and apple (Malus domestica) fruits to the exposure tests. Our results indicated that pathogenicity varies with the isolate (with C2, C8, and C10 as the most virulent), fruit condition (wounded fruits are the most susceptible), and cultivars (terra, marmela, and maça are the most susceptible). All isolates were more virulent on wounded bananas, while those on unwounded ones showed lower virulence. Among the banana cultivars, “prata” fruits were the most susceptible, regardless of wounding. Additionally, Colletotrichum isolates from dwarf bananas were pathogenic to mango, papaya, and apple fruits. Furthermore, our results demonstrated that the most virulent isolates belong to the species C. musae. Collectively, our findings reinforce the relevance of minimizing post-harvest wounds on banana fruits and highlight the risks of cross-infection when storing bananas alongside other fruit species.